Analyzing the Performance Evaluation of Senior High School Immersion Students through a Convergent Parallel Approach - Asuque, John Rafael; Pacle, Andre Jed; Mercado, Faizah Rachinee (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to analyze the performance of Senior High School work immersion students at Holy Cross of Mintal, Inc. using a convergent parallel mixed-methods approach. Grounded in experiential learning and supported by concepts of self-efficacy and career development, the study integrated quantitative performance evaluation and qualitative lived experiences to provide a comprehensive understanding of workplace readiness. A total of 197 Grade 12 students participated in the quantitative phase, while 10 purposively selected students contributed to the qualitative strand. Data were collected using a standardized performance evaluation tool with high internal consistency and an open-ended questionnaire exploring experiences, challenges, and coping strategies. Findings revealed a consistently high level of performance across all dimensions, particularly in professionalism, work ethics, and adaptability. Qualitative results showed that students underwent significant professional transformation, transitioning from initial hesitation to active workplace engagement. However, challenges such as communication apprehension, time management difficulties, emotional pressure, and unfamiliar work environments affected performance. Students employed adaptive strategies including cognitive reframing, mentorship seeking, and systematic task management to cope with these challenges. The integration of findings confirmed that while students demonstrated strong competencies, their performance was influenced by resilience in managing internal and external stressors. The study concludes that work immersion is an effective bridge between academic learning and professional practice, fostering both skill development and professional identity. It recommends enhanced pre-immersion preparation, strengthened mentorship systems, and increased support for students’ emotional and communication development. This study aligns with SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth) by promoting skills development and workplace readiness. It contributes to educational and socio-economic sustainability by improving institutional practices that prepare learners for productive participation in the workforce.
Keywords: Adaptability; Experiential learning; Mixed-methods; Performance evaluation; Work immersion